RESPON PEMBERIAN DOSIS PUPUK GUANO DAN KONSENTRASI PUPUK ORGANIK CAIR (POC) KOTORAN KAMBING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG DAUN (Allium fistulosum L.) - Sukanto, Sukanto; Mulyono, Mulyono; Toniyoga, Ichwan (Universitas Gajah Putih, 2024)
Leek plant (Allium fistulosum L.). including one type of leaf vegetable as a kitchen spice in Indonesia. This research was carried out in Linung Bulen II village, Bintang District, Central Aceh Regency, Aceh Province. Which will take place from May to August 2024. The aim of the research is to determine the effect of Guano Fertilizer Dosage and Goat Manure Liquid Organic Fertilizer (POC) Concentration on the growth and yield of leek plants (Allium fistulosum L.). This research used a randomized block design with a factorial pattern, which consisted of 2 factors, namely the first factor was the provision of Guano fertilizer, the second factor was goat manure POC. Consisting of 3 levels. First, Guano fertilizer dose which consists of 3 levels, namely: G1: 0 kg/plot, G1: 2 kg/plot, G2: 3.5 kg/plot, second, goat manure POC concentration which consists of 3 levels, namely: P1: 0 ml/1 liter of water, P2: 160 ml/1 liter of water, P2: 200 ml/1 liter of water. The results showed that there was a real interaction between the dose of guano fertilizer and the POC concentration of goat manure on the growth of leek plants (Allium fistulosum L.). Among other things, only the number of leaves aged 45 days after planting and the amount of wet fruit weight per plot at 75 days after planting leek plants.